Pembuatan Media Interaktif untuk Anak Usia Balita Belajar Membaca - Satriya Gede Jaya Wibawa; Gregorius Satia Budhi; Lily Puspa Dewi (Jurnal Infra, 2015)
Making this program aims to interest children in learning to read in a fun way, so that children in the age of the children can master the technique of reading. This is done because of demands for children aged under five are expected to master the technique of reading before they continue their education at the elementary level, but because reading is a basic foundation in communication.For application design researchers using interviews with informants, as well as the selection of the manufacturing features in interactive media.The results of this interactive medium is a game that has two menus is